The influence of TikTok water saving competition on raising climate change awareness among students in Malaysia - Mou Leong, Tan; Siti Rahyla , Rahmat; Siew Chun, Low; Mohd Amirul , Mahamud (GEOGRAFI, 2025)
TikTok is a popular social media platform with a large number of young users worldwide. In line with this, the Water Saving Competition on TikTok has been organized by the Water Watch Penang Association and USM, with sponsorship from the Penang Water Supply Corporation (PBAPP), since 2021. This study aims to analyze the impact of the Water Conservation Competition on TikTok in raising awareness among students in Malaysia, focusing on aspects of preparation, inspirational factors, effectiveness, and its contribution to achieving the Sustainable Development Goals (SDGs). A qualitative approach using thematic analysis was employed to gain an in-depth understanding, with eight participants interviewed through semi-structured sessions. The findings indicate that this TikTok competition plays a crucial role in enhancing participants’ knowledge of water conservation practices. Through participation, they develop skills in time management, planning, and collaboration with peers or family members in video production. Participants gain inspiration for their water-saving videos from previous competition experiences, everyday life situations, and existing content on social media. This competition not only helps participants increase their awareness but also benefits students involved in organizing the event, as well as the TikTok community, by enriching their knowledge of more practical water-saving strategies. After taking part in the competition, participants become more efficient in practicing water conservation and feel more motivated to spread awareness to others, aligning with SDG 6: Clean Water and Sanitation and SDG 13: Climate Action. Such initiatives should be expanded to support efforts in enhancing climate resilience and reducing disaster risks in Malaysia.